Z prawnej problematyki czasu trwania dzierżawy w prawie polskim oraz wybranych krajów Europy Zachodniej - Suchoń, Aneta (Wydawnictwo Naukowe UAM, 2014)
The aim of this article is to identify legal problems that arise from the term of a land lease. Certain solutions are proposed, also regarding the question whether the principles according to which a lease duration is actually determined to ensure the holder (tenant) stability necessary to manage the rented land and carry out business efficiently. It is concluded that in comparison to other European countries, when it comes to the regulation of a lease in the civil code in Poland, there is little interest on the part of either party in the duration of a lease. Both parties to a lease contract are granted freedom to decide upon a short or unspecified term of lease, to the effect that the concluded contracts do not secure any stability of the lease and fail to encourage tenants to make investments, or to consider long-term plans and conducting some rational management of land. Hence the authoress’ de lege ferenda conclusions proposing certain necessary amendments to the existing regulation.

Lo scopo dell’articolo era di identificare i problemi giuridici relativi alla determinazione della durata di locazione e di tentare di risolverli, ma anche di rispondere alla domanda se le regole relative alla determinazione di questo tempo garantiscano al. possessore dipendente la stabilizzazione in termini di diritto del godimento dei terreni e di svolgimento di un’attività economica. In conclusione, l’autrice ha affermato che sullo sfondo delle regolazioni dell’Europa occidentale si può osservare uno scarso interesse del legislatore nazionale per quanto riguarda la durata di locazione nel codice civile. Questo atto giuridico dà alle parti piena libertà in materia di stipulazione dei contratti di locazione dei terreni agricoli per un breve periodo o per un periodo indeterminato. I contratti in questione sono poco stabili, non incoraggiano i locatori a impiegare risorse, progettare e svolgere una razionale attività economica. Pertanto, l’autrice ha formulato le conclusioni de lege ferenda volte a configurare diversamente la durata di locazione.
Duration of a lease under Polish law and selected laws of other European states
La problematica della durata di locazione nel diritto polacco e in alcuni paesi scelti dell’Europa occidentale